Exploring the Intersection of Drug Addiction and Mental Ill-Health in Scottish Prisons: A Qualitative Study of Incarcerated Men - Deuchar, Ross (Journal of drug issues, 2024)
This article presents insights from small-scale qualitative research exploring the intertwining nature of drug addiction and mental ill-health among men in Scottish prisons. Semi-structured interviews were conducted with 24 men in two Scottish prisons. The men’s narratives suggested that increased tension in prison halls had stimulated a huge surge in the use of New Psychoactive Substances (NPS), in turn increasing and deepening existing mental ill-health and violence. They believed health care in the prisons to be of low quality, and that methadone was prescribed as a mechanism for social control. Implications for future policy, practice and research are outlined.